2021
DOI: 10.1016/j.cjco.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Testosterone on Cardiovascular Disease and Cardiovascular Risk Factors in Men: A Review of Clinical and Preclinical Data

Abstract: Cardiovascular disease (CVD) is the leading cause of death worldwide. The effects of testosterone, the primary male sex hormone, on cardiovascular risk have been of special interest due to the increased risk of CVD in men. Although it is well established that testosterone levels decline and cardiovascular mortality increases with age, the association between testosterone and CVD remains unclear. Observational and randomized studies on the effects of endogenous and exogenous testosterone have produced conflicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 101 publications
0
30
0
3
Order By: Relevance
“…The mechanisms responsible for the detrimental effect of the sex-specific lower T/E2 ratios on vascular health and clinical outcomes are not clearly elucidated. Recently, clinical studies have also explored the contribution of testosterone in cardiovascular disease [33] sometimes with contradictory results. The MrOS prospective study of 552 elderly male patients found no relationship between sex hormones levels (i.e., testosterone and T/E2 ratio quartiles) and the risk of cardiovascular events [34].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms responsible for the detrimental effect of the sex-specific lower T/E2 ratios on vascular health and clinical outcomes are not clearly elucidated. Recently, clinical studies have also explored the contribution of testosterone in cardiovascular disease [33] sometimes with contradictory results. The MrOS prospective study of 552 elderly male patients found no relationship between sex hormones levels (i.e., testosterone and T/E2 ratio quartiles) and the risk of cardiovascular events [34].…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone and estrogen are known to affect atherosclerosis in both sexes and multiple mechanisms have been postulated to play an underlying role ( 50 ). While testosterone was previously reported to improve insulin sensitivity, lower visceral adiposity and exert vasodilatory effects ( 51 ), clinical and animal research on the role of testosterone in atherosclerosis and related cardiovascular health remains inconclusive and rather contradictory ( 52 , 53 ). For instance, multiple epidemiological studies suggest that testosterone deficiency may attribute to an increased incidence of adverse cardiovascular events ( 54 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Congruently, animal studies using atherosclerotic murine models have shown that testosterone can retard atherogenesis ( 57 , 58 ), possibly via its conversion to cardioprotective estradiol in the vessel wall. Few other studies have reported a beneficial effect of short- or long-term testosterone administration on arterial stiffness and vasomotor function ( 52 ). In the current work, we found significant differences in plasma testosterone levels between MetS and non-MetS genotypes, and this difference was observed in both male and female mice.…”
Section: Discussionmentioning
confidence: 99%
“…The contemporary massive use of androgens as senolytic agents has been re-initiated by gerontologists, but now it has extended to other areas of medicine, being finally (but reluctantly) accepted by the endocrinologists probably because of the consequences of their generalized (and often uncontrolled) use [ 654 , 655 ], and especially, because part of the ravages of old age and MS are clinically improved by TRTs [ 656 , 657 ]. In addition, TRTs also help regularize glycaemia [ 658 ], maintain muscle mass [ 659 , 660 ], improve well-being [ 661 ] and reduce the development/severity of cardiovascular disorders [ 662 ]. However, the uncontrolled use of androgenic drugs has been observed to induce serious health problems, as described in Section 7.3 , including psychological and personality alterations [ 663 ] and even reproduction-related loss of function [ 664 , 665 ], including infertility [ 390 ].…”
Section: The Use Of Androgens For the Treatment Of Functional Disordersmentioning
confidence: 99%